Jesus in Islamic worldview (Quranic approach) - Ashimi, Tijani Ahmad (2015)
The more people have tried to discover who Jesus really was, the more it has been found how little is known about him. Because there are limited records of his teachings and some of his actions. As a matter of fact, very little is known about how he actually lived his life from moment to moment, and how he conducted his everyday transaction with other people.Yet, the worldview of Islam, which derives its authenticity from Qur’an respects and venerates Jesus Christ. It considers him to be one of God's greatest messengers to humankind. As such, The Qur'an (as the last of the divine books, reveled by God to the last of messenger), is undoubtedly a source of knowledge about Jesus which not generally known to some of adherents of Christianity and Judaism respectively. Indeed, the Qur’an not only leads us towards a better understanding of who he was, but also through that understanding, it increases our respect and love for him. It re-affirms his miraculous birth and his miraculous abilities. Furthermore, his mother Mary is regarded as one of the most pure and exalted women of all creation. Based on the above fact, this paper aims to explore the true nature of Jesus Christ in Islamic worldview by applying Quranic approach. That is by analyzing Quranic verses that related to Jesus Christ, the son of Mary.